The Electric Compress Lowers Body Temperature During Fever Using The PID Control System - Mayang Sari, Tri Rizki (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Compressing is a physical method for lowering the body temperature for those who are experiencing a fever. It can be done by using fluids or tools that can cause warmth and coolness to related parts of the body. The aim of developing this tool is to add a cold temperature selection mode and PID control to reduce the possibility of errors in setting the temperature with the resulting temperature in the compress, as well as getting a more stable and faster temperature adjusment. This research used an ATmega328P microcontroller as a data processor, a PID control system as a temperature controller for the heating element, an LM35 temperature sensor as a temperature detector, two heaters as hot and cold media, an I2ºC LCD as a display and a buzzer as a marker for the completion of the compress therapy process. Measurements were carried out at a hot temperature setting of 37ºC, 39ºC, and 41ºC, and a cold temperature setting of 20ºC and 25ºC. From these temperature measurements, the difference in temperature measurements between the measurements on the proposed tool module and the measurements on the thermometer at each point was, on average, below 1ºC. Therefore, this electric compressor is proven capable of operating like a real therapeutic tool.